Evaluation of the Effects of a Spellchecker on the Intellectualisation of IsiZulu. - Keet, C. Maria; Khumalo, Langa (Alternation, 2017)
Through its bilingual language policy and plan that recognises English and isiZulu as official languages of the University of KwaZulu-Natal (UKZN), UKZN has aggressively promoted the intellectualisation of isiZulu as an effective strategy in advancing indigenous, under-resourced African languages as vehicles for innovation, science, and technology research in Higher Education and Training institutions. UKZN recently launched human language technologies (HLTs) in isiZulu as enablers towards the intellectualisation of the language. One of these is an isiZulu spellchecker, which was trained on an organic isiZulu National Corpus. We evaluate the isiZulu spellchecker's effects on the intellectualisation of isiZulu. Two surveys were conducted with the target end-users, consisting of relevant questions and the System Usability Scale, and an analysis of words added to the spellchecker. It is evident that the spellchecker has had a positive impact on the work of target end-users, who also perceive it as an enabler in the intellectualisation of isiZulu. The survey responses show modest success for a first version of the tool. The analysis of the words added to the spellchecker indicates that new words are being added to the isiZulu lexicon.